DIDACTIC BASICS OF THE USE OF INFORMATION AND COMMUNICATION TECHNOLOGIES IN GERMAN LESSONS (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article analyzes the didactic foundations of the use of information and communication technologies (ICT) in the classroom of German as a foreign language from a scientific-theoretical and methodological perspective. The functional possibilities of digital learning environments, online platforms, multimedia tools, interactive methods and media resources in foreign language teaching are shown. In addition, the role of ICT in the development of communicative competence, the increase of learning motivation and the individualization of the teaching-learning process is justified.